A review of chemical reactions of nitrification intermediates and their role in nitrogen cycling and nitrogen trace gas formation in soil. (16th November 2015) - Heil, J.; Vereecken, H.; Brüggemann, N.
Summary: Soil is a major source of nitrogen trace gases (NTGs). Microbial denitrification has long been identified as a source of NTGs under reducing conditions, whereas the production of NTGs during nitrification is far from being completely understood. This review updates information about the role of abiotic processes in the formation of gaseous N products in soil and brings attention to the potential interplay of microbial and chemical soil processes that tend to be neglected in research on NTG emissions. Several reactions that involve the nitrification intermediates, nitrite (NO2 − ) and hydroxylamine (NH2 OH), are known to produce the NTGs nitric oxide (NO) and nitrous oxide (N2 O). These abiotic reactions are: the self‐decomposition of NO2 −, reactions of NO2 − with reduced metal cations, nitrosation of soil organic matter (SOM) by NO2 −, the reaction between NO2 − and NH2 OH, and the oxidation of NH2 OH by Fe 3+ or MnO2 . These reactions can occur over a broad range of soil characteristics, but they are disregarded in most current research on NTG studies in favour of biological processes only. Relatively few studies have tried to quantify the contribution of abiotic processes to total NTG emissions, which results in uncertainty in emission models and mitigation strategies. It is difficult to discriminate between biological and abiotic sources because both processes can proceed at the same time in the same soil layer. The potential of stable isotope techniques to disentangle the different processes in soil and to constrain budgets of atmospheric NTGs better are highlighted. Recent advances in stable isotope technologies, such as infrared real‐time laser spectroscopy, provide considerable potential for both natural abundance and tracer studies in this field.